2017
DOI: 10.1002/ijc.31109
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on stage specific prostate cancer survival and mortality before and after introduction of PSA test in Finland

Abstract: Socioeconomic status (SES) has an impact on prostate cancer (PCa) outcomes. Men with high SES have higher incidence and lower mortality of PCa versus lower SES males. PCa cases diagnosed in Finland in 1985-2014 (N = 95,076) were identified from the Finnish Cancer Registry. Information on education level (EL) was obtained from Statistics Finland. EL was assessed with three-tiered scale: basic, upper secondary and higher education. PCa stage at diagnosis was defined as localized, metastatic or unknown. Years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, patients with higher education levels have increased postoperative PSA frequency, which reflects the need to strengthen patient follow-up guidance further. This conclusion is similar to that in Seikkula’s previous study, which found that patients with higher education levels had more PSA testing [ 31 ]. For patients with lower education levels, proactive telephone, and Internet follow-up were used to understand their postoperative recovery, resolve their disease questions, and provide personalized guidance.…”
Section: Discussionsupporting
confidence: 91%
“…However, patients with higher education levels have increased postoperative PSA frequency, which reflects the need to strengthen patient follow-up guidance further. This conclusion is similar to that in Seikkula’s previous study, which found that patients with higher education levels had more PSA testing [ 31 ]. For patients with lower education levels, proactive telephone, and Internet follow-up were used to understand their postoperative recovery, resolve their disease questions, and provide personalized guidance.…”
Section: Discussionsupporting
confidence: 91%
“…In China, the annual incidence of PCa was more than 60,000 cases and 26,600 patients who succumbed to PCa in 2015 [6]. The majority of early-stage PCa patients have an excellent prognosis with a low mortality rate [7]. However, there are still a large number of PCa patients who develop the resistance to androgen deprivation therapy (ADT) and become castrationresistant PCa (CRPC), which results in a short survival time [8].…”
mentioning
confidence: 99%
“…In general, localized PCa patients with lower SES have a higher comorbidity burden and poorer lifestyle (such as smoking, lack of exercise, obesity), which might affect the outcome of the patients ( 20 ). Furthermore, high SES may provide timely and high-quality cancer care ( 30 ).…”
Section: Discussionmentioning
confidence: 99%